Social capital and political institutions: Evidence that democracy fosters trust - Martin Ljunge (Research Institute of Industrial Economics (IFN), 2013)
This paper finds evidence that more democratic political institutions increase trust. Second generation immigrants with ancestries from 115 countries are studied within 30 European countries. Comparing individuals born and residing in the same country, those whose father was born in a more democratic country express higher trust than those whose father was born in a less democratic country. The results are robust to individual, parental, and ancestral country controls.
Keywords: F55; H10; J62; Z13; 330; trust; democracy; political institutions; cultural transmission; social capital